Implementasi Metode Certainty Factor Dalam Mendeteksi Hama Dan Penyakit Pada Jamur Tiram Putih - Nia Ade Do; Dewi Suranti; Eko Suryana (UNIVED Press, 2024)
White oyster mushroom (Pleurotus ostreatus) is a type of mushroom that is semicircular in its hood so that it is similar to an oyster shell with a slightly concave center. In the oyster mushroom cultivation business, it is not free from the risk of losses that arise if the cultivator is not diligent and careful in maintaining oyster mushrooms. New cultivators have difficulty identifying pests or pests that attack oyster mushroom plants so that the prevention that will be carried out in handling the maintenance process of oyster mushroom plants is less precise. The implementation of certainty factor method in detecting pests and diseases in white oyster mushrooms at Rafflesia Mushrooms can make it easy to find out information and procedures for dealing with pests and diseases in White Oyster Mushrooms by entering the symptoms experienced by the white oyster mushroom. The application of the implementation of certainty factor method in detecting pests and diseases in white oyster mushrooms at Rafflesia Mushrooms is made using PHP programming language and MySQL database, which can be accessed online via the link http://hamapenyakitjamurtiramputih.my.id. To determine the level of confidence in the symptoms felt against pests and diseases of white oyster mushrooms based on the user's CF value and the expert's CF value. Based on the black box method testing that has been carried out, it can be concluded that the functional of the application has run well and can provide consultation results on diagnosing pests or diseases experienced by white oyster mushrooms based on symptoms that have been selected by the user through Certainty Factor method stage.